In the Iberian Peninsula and Beyond: A History of Jews and Muslims (15th-17th Centuries) - Tavim, José Alberto R. Silva (2015)
This book is the result of two scientific encounters hosted by the University of Évorain 2012, with the theme “Muslims and Jews in Portugal and the Diaspora. Identities and Memories (16th – 17th centuries)”, and co-financed by the Foundation for Science and Technology, and by FEDER, through “Eixo I” of the “ProgramaOperacionalFatores de Competitividade” (POFC) of QREN (COMPETE).Beginning with an analysis of the forced conversion of Iberian Jews and Muslims, this volumeexamines the effects of this on their respectivediasporas and/or permanencies as New-Christians in their original Kingdoms, focusing on a variety of approaches, from language and culture to identity discourses and interchanges between those communities.